KEBERLANJUTAN USAHA PETERNAKAN AYAM RAS PEDAGING PADA POLA KEMITRAAN SUSTAINABILITY OF BROILER FARMING ON PARTNERSHIP PATTERN - SURYANTI, RENI (Perum BULOG, 2019)
The low level of sustainability of the broiler farming related to the low business capacity of farmers. This condition causes sustainability were low at economic, ecological and social dimension. The study aims to analyze the level of sustainability of broiler farming on partnership pattern, and analyze the influence of capacity on the sustainability ts business. The study involved 247 broiler farmers in Sukabumi and Bogor Regency. The research was conducted from August to October 2018. Samples were determined by cluster random sampling technique with farmer clusters in two districts. Data analysis used descriptive analysis and inferencing with regression and correlation. The results show that siustanibility were low. The business capacity of broiler farmers were weak. The low level of business sustainability is supported by the weak ability of non-technical farmers. Economic sustainability is positively related to technical ability and entrepreneurship. Ecological sustainability has positively related to technical and managerial capabilities. Whereas social sustainability relates negatively to technical, managerial and entrepreneurial abilities. Enhancing technical capabilities is needed to support business sustainability. A significant relationship between technical capabilities, entrepreneurship, managerial and economic, ecological and social sustainability can be followed up by giving attention to these capabilities in the implementation of extension activities.